(untitled) (ENTHYMEMA, 2016)
The Narratology of new generation shows renewed heuristic scenarios, providing an intense dialogue among Humanities, Cognitive Neuroscience and Computer Technology. The suspense case is emblematic: its spread and the pleasure exercised by this rhetorical strategy on the human mind can be precisely explained by identifying the mechanisms of reward provided by neurological and Imaging studies. At the same time, patterns of automatic generation of narrative highlight the profound implications of a heated debate between Narratology and Computer Technology, in order to understand the processes of reception and inference during the narrative immersion in storyworlds. At the end of overview on of a cross-disciplinary approach of suspense analysis, the authors repost a case study considered of interest, provided by the North Caroline State University researchers group, called Liquid Narrative Group.